Manejo da giberela do trigo e manifestação do potencial toxigênico em diferentes sistemas de cultivo - Agápto, João Paulo (Universidade Federal de São Carlos, 2024)
Wheat Fusarium Head Blight (Gibberella zeae Schwein, Fusarium graminearum) is one of the most important diseases of this cereal worldwide, causing damage to grains in the form of atrophy, weight reduction, and discoloration. Besides yield loss, it also results in grain contamination by mycotoxins, posing a risk to human and animal health. Thus, managing the disease is a significant challenge for global wheat cultivation. No single strategy used in isolation provides satisfactory reduction of disease intensity and mycotoxin concentration under conditions favorable for pathogen development. This study aimed to evaluate the technical feasibility of integrating fungicide, genetic resistance, and silicon in managing Gibberella in irrigated and rainfed production systems. The experiments were conducted using a randomized complete block design with three replications and four treatments, namely: T1 – Fungicide + Potassium Silicate (F + SK) application; T2 – Fungicide (F) application; T3 – Potassium Silicate (SK) application; and T4 – Control (no F and SK application). In all experiments, the incidence, severity, and index of Gibberella, as well as mycotoxin concentration and productivity, were quantified. After performing variance analysis and Tukey's test (p<0.05). It was found that there was no significant difference between treatments for the agronomic variables. For the laboratory variables, T3 was the treatment that provided the greatest reduction in DON concentration, but it did not differ statistically from T1 and T2. It is concluded that the application of potassium silicate (PS) should be further explored for the reduction of DON. The application of PS may be an alternative in integrated management proposals for controlling wheat scab.
Management of wheat fusarium head blight and manifestation of toxigenic potential in different cultivation systems
Keywords: Gibberella zeae; Controle químico; Variedade resistente; Silicato de potássio; Micotoxinas; Chemical control; Resistant variety; Potassium silicate; Mycotoxins; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::FITOPATOLOGIA